Effect of Vitamin A on Infertility Induced by Aluminum Chloride in Male Albino Mice - Zainab EL Mabrouk; Habiba El Jaafari; Samira Elghul; Naema Shibani; Salma Abusrer (AlQalam Journal of Medical and Applied Sciences, 2021)
Aims. The present study was designed to investigate the reproductive toxicity of Aluminum chloride (AlCl3), and the potential protective role of vitamin A in adult male mice. Methods: Twenty-one adult male albino mice were divided into three equal groups, the first group injected with distilled water, the second group injected with AlCl3 (120 mg/kg BW) daily for 10 days. The third group was also injected with AlCl3 (120 mg/kg BW) for 10 days, then injected with vitamin A (40 mg/kg) for another 10 days. All doses were given once daily via intraperitoneal injection. Results: The results showed that AlCl3 cause significant decrease in body weight, sperm motility, and sperm count, while it led to a significant increase in the number of abnormal sperm morphology. AlCl3 caused apparent alterations in the histological structure of the testes. While treatment with vitamin A showed a protective effect on the damage caused by AlCl3, on body weight, sperm parameters, and histoarchitecture of mice testes in comparison with AlCl3 treated mice. Conclusion: This study affords evidence for the protective role of vitamin A in ameliorating testicular toxicity caused by AlCl3.